Alternative strategies for Chlamydia treatment: Promising non-antibiotic approaches - Hou, Chen; Jin, Yingqi; Wu, Hua; Li, Pengyi; Liu, Longyun; Zheng, Kang; Wang, Chuan (Frontiers in Microbiology, 2022)
Chlamydia is an obligate intracellular bacteria most of which is pathogenic and infectious, causing a variety of infectious diseases and complications in humans and animals. Antibiotics are often recommended for the clinical treatment of chlamydial infection. However, an accumulating body of studies shown that, antibiotics may not be enough to wipe out chlamydial infection and inhibit infection completely as well as have some potential risks including antibiotic resistance. In public health, the impact on chlamydial infection and antibiotic abuse cannot be underestimated. This paper reviews the recent researches on the prevention and suppression of chlamydial infection by non-antibiotic anti-chlamydial compounds, and the development potential for new therapeutic methods are discussed.